Design of A Flexible Table Height (Kafleks) with Quality Function Deployment (QFD) Method - Ika Nurlela; Risma Fitriani (OPSI, 2022)
Humans have high mobility and various activities for each individual. The table is one of the supporting facilities in human activities. The table can have an important effect in terms of user mobility in using it. A table that is comfortable for users can provide a good and maximum effect for users in completing all their activities. The height of the table is one of the influential aspects in determining whether the table is comfortable or not for its users. This research is aimed at designing and developing a table product with high legs that can adapt to various conditions and activities carried out. The method used in this study is the Quality Function Deployment (QFD) method. The result of this study is that the adjustable table height has a degree of importance of 4 which means that this aspect is important for a table to have.